PKC-dependent activation of human K2P18.1 K+ channels - Rahm, Ann-Kathrin; Gierten, Jakob; Kisselbach, Jana; Staudacher, Ingo; Staudacher, Kathrin; Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (British journal of pharmacology, 2012)
BACKGROUND AND PURPOSE Two-pore-domain K+ channels (K2P) mediate K+ background currents that modulate the membrane potential of excitable cells. K2P18.1 (TWIK-related spinal cord K+ channel) provides hyperpolarizing background currents in neurons. Recently, a dominant-negative loss-of-function mutation in K2P18.1 has been implicated in migraine, and activation of K2P18.1 channels was proposed as a therapeutic strategy. Here we elucidated the molecular mechanisms underlying PKC-dependent activation of K2P18.1 currents. EXPERIMENTAL APPROACH Human K2P18.1 channels were heterologously expressed in Xenopus laevis oocytes, and currents were recorded with the two-electrode voltage clamp technique. KEY RESULTS Stimulation of PKC using phorbol 12-myristate-13-acetate (PMA) activated the hK2P18.1 current by 3.1-fold in a concentration-dependent fashion. The inactive analogue 4α-PMA had no effect on channel activity. The specific PKC inhibitors bisindolylmaleimide I, Ro-32-0432 and chelerythrine reduced PMA-induced channel activation indicating that PKC is involved in this effect of PMA. Selective activation of conventional PKC isoforms with thymeleatoxin (100 nM) did not reproduce K2P18.1 channel activation. Current activation by PMA was not affected by pretreatment with CsA (calcineurin inhibitor) or KT 5720 (PKA inhibitor), ruling out a significant contribution of calcineurin or cross-talk with PKA to the PKC-dependent hK2P18.1 activation. Finally, mutation of putative PKC phosphorylation sites did not prevent PMA-induced K2P18.1 channel activation. CONCLUSIONS AND IMPLICATIONS We demonstrated that activation of hK2P18.1 (TRESK) by PMA is mediated by PKC stimulation. Hence, PKC-mediated activation of K2P18.1 background currents may serve as a novel molecular target for migraine treatment.